TELAAH FITOKIMIA KULIT KACANG TANAH (Arachis hypogaea, L). - Rizki Nisfi Ramdhini; Isna Mulyani; Syaikhul Aziz (JFL : Jurnal Farmasi Lampung, 2021)
Peanut peel are a waste product of the peanut processing industry with little commercial value. Some of studies have been conducted indicating peanut peel can be beneficial as a source for traditional medicinal products since it is also rich of antioxidants. The aim of this research was to identify the content of secondary metabolites on the peanut peel. The method used was maseration with 96% ethanol. Phytochemical screening and assaying were performed using thin layer chromatography (TLC) method. The results of TLC analysis showed that the secondary metabolites in peanut peel were positive for flavonoids, alkaloids, tannins and quinon. Keywords: Peanut peel, Phytochemical, Thin-Layer chromatography (TLC)